2013
DOI: 10.2220/biomedres.34.31
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of gingival inflammation induced by synergism of IL-1^|^beta; and IL-6

Abstract: Internleukin-1 (IL-1) and IL-6 are the most potent proinflammatory cytokines being involved in inflammatory diseases such as periodontitis. The objective of this study was to examine the synergistic effects of IL-1β and IL-6 on gingival inflammation by targeting cultured human gingival fibroblasts (HGFs). HGFs were treated with IL-1β or IL-6/soluble IL-6R (sIL-6R), and total RNA and total cell lysate were collected to examine expression of gp130 known as a signal transducer of IL-6 using qRT-PCR and Western bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
73
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 68 publications
(78 citation statements)
references
References 33 publications
3
73
0
2
Order By: Relevance
“…Furthermore, we showed previously that IL-6 binding to HGFs increases significantly in the presence of sIL-6R [20]. Considering the possible source of sIL-6R in periodontitis lesions, we reported that sIL-6R production was induced by IL-6 and CPT in THP-1 macrophages [7,21]. Importantly, we showed that CPT-mediated induction of sIL-6R inhibited significantly in THP-1 macrophages by TACE specific inhibitor, TAPI-1 (Fig.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Furthermore, we showed previously that IL-6 binding to HGFs increases significantly in the presence of sIL-6R [20]. Considering the possible source of sIL-6R in periodontitis lesions, we reported that sIL-6R production was induced by IL-6 and CPT in THP-1 macrophages [7,21]. Importantly, we showed that CPT-mediated induction of sIL-6R inhibited significantly in THP-1 macrophages by TACE specific inhibitor, TAPI-1 (Fig.…”
Section: Discussionmentioning
confidence: 52%
“…In addition, TIMPs are considered to be important molecules to regulate the actions of MMPs [25], and a disturbed balance of MMPs and TIMPs should be involved in the progression of periodontitis [26]. IL-1β and IL-6 may be responsible to the tissue destruction by increasing MMPs from HGFs [21]. In view of severe periodontitis in diabetic patients, therefore, we examined the effects of HG on IL-1β or IL-6-induced MMP-1 and TIMP-1 in HGFs.…”
Section: Discussionmentioning
confidence: 99%
“…Fibroblasts constitutively express a low level of IL-6. Furthermore, IL-1 and TNF-α synergistically enhance the production of IL-6 by fibroblasts (31)(32)(33). IL-1β and TNF-α induce NF-κB expression, and then NF-κB subsequently controls the expression of IL-1β, IL-6 and TNF-α (34)(35)(36).…”
Section: Discussionmentioning
confidence: 99%
“…IL-1Ra levels in gingival crevicular fluid (GCF) are negatively correlated with disease severity in chronic periodontitis patients (18), while IL-1Ra levels in moderate and deep pockets from patients with aggressive periodontitis were lower than those at control sites (19). In contrast, IL-1Ra mRNA expression was found to be upregulated with IL-1␤ or the IL-6/soluble IL-6 receptor (sIL-6R) complex in inflamed human gingival tissue (20). Peripheral blood mononuclear cells from patients with generalized aggressive periodontitis exhibited higher levels of IL-1Ra and IL-10 than those from healthy controls with or without LPS stimulation (21).…”
mentioning
confidence: 99%